Walter Scott and Blackwood's: Writing for the Adventurers. Issue 3 (October 2017) - Lumsden, Alison
Abstract : The significance of Scott as a literary and cultural critic is little understood. Yet Scott was a lively participant in journal culture and contributed to it throughout his publishing career, writing for Blackwood's from its inception in 1817 until near the end of his life in 1829. Scott established himself as one of the finest critics and reviewers of his day, offering pertinent remarks on, among others, Byron, Mary Shelley, and Austen. This article explores Scott's contributions to Blackwood ' s, his reasons for publishing in this often combative space, and the ways in which it offers Scott an opportunity to explore new aspects of his creativity. It pays attention to Scott's pieces on Scottish gypsies and to his iconic review of Frankenstein . It also examines his forays into the genre of 'tale', the ways in which they facilitate the development of the short story, and how they contribute to the development of Scott's career.